The Relationship between Body Mass Index and Dental Development by Demirjian's Method in 4- to 15-Year-Old Children in Mashhad - Najmeh Anbiaee; Anousheh Rashed Mohassel; Ali Bagherpour (Mashhad University of Medical Sciences, 2013)
Introduction: The purpose of this study was to evaluate the relationship between the body mass index (BMI) and dental development. Methods: The dental ages of 196 children were calculated according to Demirjian's method. The chronological age, weight, and height were recorded. Dental development was defined as dental age minus chronological age. Children were classified into three groups according to their BMI: underweight, normal, or overweight and obese. We used One-way analysis of variance (ANOVA), and Pearson correlation tests to analyze the data (significance level of 0.05). Results: There was a significant correlation between BMI and dental development in the girls (P=0.03, r=0.205). There was not a significant correlation between BMI and dental development in the boys (P=0.08, r=0.18). There was not a significant difference between the mean dental development and BMI group in the girls (P=0.07). There was a significant difference between mean dental development in different BMI groups in the boys (P=0.018). Conclusion: Dental development in overweight and obese boys is significantly accelerated